Peran Literasi Digital Dalam Membangun Kesadaran Dan Moralitas Peserta Didik Sesuai Dengan SDGs 2030 - Adelia Dhea Oktria; Via Musaffa; Ichsan Fauzi Rachman (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research is motivated by the lack of online moral and ethical awareness regarding the presence of technology in the lives of learners who were born and grew up alongside the digital era, synonymous with the development of science and technology. Therefore, this study aims to discuss the role of digital literacy in fostering awareness and morality among learners to align with the Sustainable Development Goals (SDGs) 2030. Digital literacy now holds crucial skills in the digital age, particularly in assisting learners to understand and manage information wisely. This research employs a literature review method, utilizing a qualitative descriptive approach to analyze the role of digital literacy in enhancing awareness and morality, focusing on a case study to draw conclusions. The research has yielded results indicating that effective digital literacy can aid learners in developing awareness and morality. SDGs 2030 represent an interconnected system with mutual influence. The researcher hopes that this study can offer new insights into the potential of digital literacy to strengthen moral and ethical values within educational curricula, aiming to achieve SDGs 2030.